DNA adjuvant Amiloride conjunct long immunization interval promote higher antibody responses to HIV-1 gp41 and gp140 immunogens. Issue 47 (3rd November 2020) - Yao, Lan; Wang, Jia-Ye; Bao, Li-Na; Fan, Meng-Xuan; Bai, Yang; Chen, Wen-Jiang; Yuan, Chen; Yuan, Li; Wang, Jing; Li, Yan; Zhuang, Min; Ling, Hong
Highlights: Amiloride as a DNA adjuvant can promote humoral immune responses after protein boosts. Long immunization interval is benefit for the production of specific binding Abs. Amiloride & long interval show better immune effect than elevating immunization times. Q577A mutants of gp140 and gp41 show different immune effects compared to wild type. Abstract: Recent studies have revealed that the interface of gp120 and gp41 and some parts of gp41 are also critical epitopes for elicitation of broadly neutralizing antibodies. Therefore, potential trimeric gp41 or gp140 immunogen candidates are needed. Previously, we developed a trimer motif MTQ and demonstrated that it could help formation of trimeric gp120 and gp140 proteins. In the present study, we immunized Balb/c mice using trimeric gp41-expressing plasmid for prime and monomeric gp41 or trimeric gp140 protein as well as a mutant (Q577A) for boost. The antibody responses in the context of regimens with various immunization intervals and DNA adjuvants including praziquantel (PZQ), cimetidine (CIM), and amiloride (AML) were evaluated. We found that these three adjuvants were not enough to elicit remarkable specific Abs after gp41 DNA immunization, while AML could significantly promote humoral immune responses after protein boosts. Long immunization interval could induce the specific binding Abs earlier and higher and maintain a high level of Abs in the following 27 weeks after final protein boost. Moreover, two times of protein boosts with DNA adjuvant and a longer time interval achieved a higher titer of specific Abs than three times of protein boosts with a shorter time interval. Q577A mutant was benefit for trimeric gp140 boost in the production of binding Abs but harmful to inducing neutralizing Abs, while this mutant in monomeric gp41 presented the opposite trend which may be associated with the immunogen structures. This study highlights the significance of DNA adjuvant Amiloride and long immunization interval in promoting antibody responses and provides new insights into effective HIV immunization regimen design in the future.